Isolation, Identification, Prevalence, and Genetic Diversity of Bacillus cereus Group Bacteria From Different Foodstuffs in Tunisia - Gdoura-Ben Amor, Maroua; Siala, Mariam; Zayani, Mariem; Grosset, Noël; Smaoui, Salma; Messadi-Akrout, Feriele; Baron, Florence; Jan, Sophie; Gautier, Michel; Gdoura, Radhouane (Frontiers in Microbiology, 2018)
B. cereus group is widespread in nature and foods. Several members of this group are recognized as causing food spoilage and/or health issues. This study was designed to determine the prevalence and genetic diversity of the B. cereus group strains isolated in Tunisia from different foods (cereals, spices, cooked food, fresh-cut vegetables, raw and cooked poultry meats, seafood, canned and dairy products,). In total, 687 different samples were collected and searched for the presence of the B. cereus group after selective plating on MYP agar and enumeration of each sample. The typical pink-orange uniform colonies surrounded by a zone of precipitate were assumed to belong to the B. cereus group. One typical colony from each sample was subcultured and preserved as cryoculture. Overall, 191 (27.8%) food samples were found positive, giving rise to a collection of 191 B. cereus- like isolates. The concentration of B. cereus- like bacteria were below 103 cfu/g or ml in 77.5% of the tested samples. Higher counts (> 104 cfu/g or ml) were found in 6.8% of samples including fresh-cut vegetables, cooked foods, cereals and pastry products. To verify whether B. cereus- like isolates belonged to the B. cereus group, a PCR test targeting the sspE gene sequence specific of the group was carried out. Therefore, 174 isolates were found to be positive. Food samples were contaminated as follows: cereals (67.6%), pastry products (46.2%), cooked food (40.8%), cooked poultry meat (32.7%), seafood products (32.3%), spices (28.8%), canned products (16.7%), raw poultry meat (9.4%), fresh-cut vegetables (5.0%), and dairy products (4.8%). The 174 B. cereus isolates were characterized by partial sequencing of the panC gene, using a Sym’Previous software tool to assign them to different phylogenetic groups. Strains were distributed as follows: 61.3%, 29.5%, 7.5% and 1.7% in the group III, IV, II and V, respectively. The genetic diversity was further assessed by ERIC-PCR and PFGE typing methods. PFGE and ERIC-PCR patterns analysis allowed discriminating 143 and 99 different profiles, respectivey. These findings, associated to a relatively higher prevalence of B. cereus group in different foods, could be a significant etiological agent of food in Tunisia.